Factors influencing Malaysian public attitudes to agro-biotechnology - Amin, Latifah; Ahmad, Jamil; Md Jahi, Jamaluddin; Md Nor, Abd Rahim; Osman, Mohamad; Mahadi, Nor Muhammad (SAGE Publications, 2011)
Despite considerable research in advanced countries on public perceptions of and attitudes to modern biotechnology, limited effort has been geared towards developing a structural model of public attitudes to modern biotechnology. The purpose of this paper is to identify the relevant factors influencing public attitudes towards genetically modified (GM) soybean, and to analyze the relationship between all the attitudinal factors. A survey was carried out on 1,017 respondents from various stakeholder groups in the Klang Valley region. Results of the survey have confirmed that attitudes towards complex issues such as biotechnology should be seen as a multifaceted process. The most important factors predicting support for GM soybean are the specific application-linked perceptions about the benefits, acceptance of risk and moral concern while risk and familiarity are significant predictors of benefit and risk acceptance. Attitudes towards GM soybean are also predicted by several general classes of attitude.